Soreness or sng: a common symptom with differential clinical impact from pain in degenerative lumbar spine diseases - Chih-Cheng Chen; Yi-Chen Chen; I-Wen Su; Yu-Wen Yu; Jiann-Her Lin; Hsiao-Yean Chiu (BMJ Open Quality, 2023)
Introduction Soreness is a common complaint in patients who receive lumbar spine surgery (LSS) for degenerative lumbar spine diseases (DLSD). However, soreness is not assessed independently and its impacts on outcomes of LSS remains largely unknown. Sng(pronounced sә-ng, 痠) in Chinese language is the word with the closest meaning to soreness, and Chinese-speaking people naturally use sng to describe their non-pain ‘soreness’ symptom. This study was aimed to investigate the prevalence and impacts of soreness or sng on outcome of LSS by introducing Visual Analogue Scale (VAS) of sng on back and leg.Materials and methods This prospective cohort study recruited patients who receive LSS for DLSD. Participants completed the patient-reported outcome measures at 1 week before and 1 years after LSS. The patient-reported outcome measures included (1) VAS for back pain, leg pain, back sng and leg sng, (2) Oswestry Disability Index (ODI) and (3) RAND 36-item Short Form Health Survey. The minimal clinical important difference (MCID) of ODI and physical component health-related quality of life (HRQoL) was used.Results A total of 258 consecutive patients were included and 50 dropped out at follow-up. Preoperatively, the prevalence of sng was comparable to pain both on back and leg; postoperatively, the prevalence of sng was higher than pain. Leg and back sng were associated with preoperative and postoperative mental HRQoL, respectively. The reduction of sng on back and leg were significantly less than pain postoperatively. Leg sng was the only symptom independently associated with attaining MCID.Conclusion Soreness or sng should be assessed independently from pain in patients receiving LSS for DLSD because soreness or sng had substantial clinical impacts on the outcome of LSS.